The Effect of Monetary Policy on Foreign Trade in Nigeria - O., Ashamu Sikiru (Australian Finance & Banking Review, 2020)
This research work investigated the impact of monetary policy on foreign trade in Nigeria during the period 1981 to 2017. The research made use of secondary data which are collected from the Central Bank of Nigeria, Statistical Bulletin (2017). The model obtained from the result represents a Error Correction Model (ECM) which relates the dependent variable (Net Import) to several predictor variables Money Supply, Interest Rate, Exchange Rate, Foreign Direct Investment and Trade Openness. From the findings of the study, the error correction term (speed of adjustment towards equilibrium) value of -0.53581 is significant at 5% and implies that there is a long run causality running from monetary policy activities measures of foreign trade. However, only all the variable was used in the study was significant at 5% level of significance. This implies that monetary policy in Nigeria has a positive influence on foreign trade within the period, except for interest rate that has a negative coefficient and not significant. In conclusion, these intermediate variables of monetary, the exchange rate arguably have a huge impact on the economy because of its effect on the value of local currency, domestic inflation, macroeconomic credibility, capital flows and financial stability. Increased exchange rate directly affects the prices of imported commodities and an increase in the price of imported goods and services contributes directly to increase in inflation. Based on the analysis, the study concluded that there is significance relationship between money supply and net import in Nigeria and also that there is relationship between foreign direct investment and net import in Nigeria. The study also shows that there is relationship between trade openness and net import in Nigeria.